The ooze - Roos, Stephen; Stine, R. L.; Copyright Paperback Collection (Library of Congress) (New York : Pocket Books, 1996)
When Al invents a stink bomb that doesn't explode, he thinks his chemistry set is a dud. But when the bomb starts to ooze all over the cat and Al's best friend, they are changed forever. And the ooze is heading straight for him.
"A Minstrel book."
"A Parachute Press book."
Keywords: Horror tales; Chemistry -- Fiction; Children's stories; Ghost stories